MODIS Observed Spatiotemporal Variation of Snow Cover in Zanskar Valley, North-Western Himalaya - Khali, Harish; Pandey, Pratima; Ali, Sheikh Nawaz; Champatiray, Prashant K. (Frontiers in Water, 2022)
Investigation of the changes in the snow cover in response to the ongoing climate change is critical for the understanding of hydrological and climatological processes in Himalaya. Apart from contributing significantly to river runoff, the extent of the snow cover is also important for glacier nourishment, melting dynamics, and the intensity of the summer monsoon. Considering that the meteorological data is scarce and unevenly distributed in this region, remote sensing studies become particularly crucial. In this study, we use the Moderate Resolution Imaging Spectroradiometer (MODIS) eight-day snow cover product (MOD10A2) from 2000 to 2017 to investigate the spatiotemporal characteristics and trends of snow cover percentage in Zanskar valley. Our results suggest no significant decrease in the percentage of snow cover in the Zanskar valley in the last 17 years. The annual average snow cover in Zanskar is 67% with a maximum in the month of March (96%) and minimum in August (28%). Trend analysis show no change in the snow cover below an altitude of 3500 m above mean sea level (asl) during last 17 years. The majority of the changes in snow cover percentage occurred between an altitude of ~4500 and 5500 m asl. An overall positive trend in the percentage of snow cover was observed from 2000 to 2017. The snow cover data was also compared to the Climatic Research Unit's station interpolated data (CRU) to look into any significant inconsistency; however any significant incongruity was not observed.